Political Configuration of Electoral System Law in Indonesia from State Administration Perspective - Saiful Risky; Sholahuddin Al-Fatih; Mabarroh Azizah (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2023)
The massive number of money politic and clientelism cases occurring between legislative electoral candidates and the community should be eradicated, especially as the general election comes close. This article analyzed the causes of money politic and clientelism in the electoral system and which electoral system that Indonesia as a state should pursue in the legal political context. This normative juridical research discussed the subjects from the point of view of positive legal norms in Indonesia and focused on a statutory approach. The research data were collected by reviewing various literatures. From the research findings, it was concluded that the open-list proportional electoral system in Indonesia in Law No. 7 Year 2017 concerning General Election should be changed into a close-list one considering that the legal politic of the Law on General Election led to the many money politic cases occurring before and after the election. The Constitutional Court in its decision No. 144/PUU-XX/2022 rejected entirely the application for a change of proportional electoral system in the Law on General Election for many considerations and the upcoming general election in 2024 would still use the open-list proportional electoral system. Nevertheless, in the national legal political context, the party drafting the Law on General Election was authorized by the Constitutional Court to change the electoral system in the future on various requirements that they need to fulfill.